2001
DOI: 10.1002/nag.159
|View full text |Cite
|
Sign up to set email alerts
|

Solutions of pore pressure build up due to progressive waves

Abstract: SUMMARYThe analytical solution of soil pore pressure accumulations due to a progressive wave is examined in detail. First of all, the errors contained in a published analytical solution for wave-induced pore pressure accumulation are addressed, and the correct solution is presented in a more general form. The behaviour of the solution under di!erent soil conditions is then investigated. It is found that the solution for deep soil conditions is sensitive to the soil shear stress in the top thin layer of the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 13 publications
0
22
0
3
Order By: Relevance
“…Liquefaction due to wave loading. The passage of large waves, either via storms or tsunami, induces oscillatory fluctuation in the loading condition, as well as progressive increase in pore pressure after repeated wave cycles (e.g., Cheng et al 2001). As successive waves pass, an undrained loading condition occurs, increasing pore fluid pressures and potentially bringing a slope closer to its static failure condition.…”
Section: Distinguishing Hyperpycnal Underflows and Storm Wave-generatmentioning
confidence: 98%
“…Liquefaction due to wave loading. The passage of large waves, either via storms or tsunami, induces oscillatory fluctuation in the loading condition, as well as progressive increase in pore pressure after repeated wave cycles (e.g., Cheng et al 2001). As successive waves pass, an undrained loading condition occurs, increasing pore fluid pressures and potentially bringing a slope closer to its static failure condition.…”
Section: Distinguishing Hyperpycnal Underflows and Storm Wave-generatmentioning
confidence: 98%
“…These analytical solutions are useful for both engineers and researchers, as they can be used for either the investigation of qualitative behaviour of complicated engineering problems or the validation of numerical methods. Recently, using a similar approach, Cheng et al [17] re-examined the analytical solution of McDougal et al [16] and proposed a numerical model to investigate the same problem. As pointed out by Cheng et al [17], the analytical solution proposed by McDougal et al [16] revealed some errors in the formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using a similar approach, Cheng et al [17] re-examined the analytical solution of McDougal et al [16] and proposed a numerical model to investigate the same problem. As pointed out by Cheng et al [17], the analytical solution proposed by McDougal et al [16] revealed some errors in the formulations. However, after a close…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed and Rahman [7] may be the first to investigate a simple 1-D finite element model to describe the build-up of pore pressure under progressive wave. This model has been further extended or modified to examine the wave-induced residual response analytically and numerically [8,[31][32][33]. Sassa and Sekiguchi [34] developed a 2-D elasto-plastic constitutive model where the principal stress axes rotation in the sand is incorporated and compared the numerical solutions with their experimental measurements conducted in a centrifuge wave tank [35].…”
Section: Introductionmentioning
confidence: 99%